Chikungunya Viral Infection Requiring Intensive Care – Experience in a Tertiary Care Hospital in Bangladesh (BIRDEM Medical Journal, 2017)
Background: Chikungunya fever is a benign self-limiting viral illness. Although it is considered as a nonfatal disease but in elderly patients who have co-morbidities can present with atypical life threatening clinical menifestations which may cause significant morbidity and mortality.The Aim of this study is to observe atypical presentations ,various complications and outcome of chikungunya fever.Methods: This was a cross sectional observational study was carried out on 23 adult patients with chikungunya fever from 1st June to 31st July of 2017 in the Department of Critical Care Medicine of BIRDEM General Hospital, Dhaka, Bangladesh.Results: Total 23 patients were included in this study, male 83% and female 17%.From indoor 17(73.9%) patients got admitted in ICU, 3(13%) patients came directly from home and 3(13%) patients from another hospitals. Most of the patients were elderly having co-morbidities like diabetes, Hypertension, IHD and CKD. COPD and CVD were also present in a few numbers of patients. Most of the patients had fever , arthralgia and headache but respiratory distress (73.9%), altered mental status (56.5%), vomiting (21.7%), diarrhoea (17.3%) and low urine output (17.3%) are the causes of ICU admission. Major Organ involvement of the study subjects were respiratory system (52.1%), renal system (47.8%), CVS (34.7%) and nervous system (34.7%). Among 23, 16(70%) patients improved and 4(17%) patients died in ICU.Conclusion: This study highlights that though chikungunya fever is considered as a benign non-fatal disease it can produce life threatening clinical menifestations and serious complications requiring Intensive Care particularly in elderly comorbid patients and can cause high mortality.Birdem Med J 2018; 8(1): 16-20